The shelter of god's promises - Walsh, Sheila (Nashville, TN Thomas Nelson, 2011)
You know God's promises, but are they for you, are they for now, are they for this? If you look to your circumstances alone, it may seem that God has forgotten you. But he hasn't. He can't. And He wouldn't even if He could. God is the only promise maker who is always a promise keeper. And God's promises will never fail you!